Economic integration : the East African experience - Hazelwood, Arthur (Heinemann LondonGB, 1975)
Outlines the historical development of the East African community of Kenya, Tanzania and Uganda. Analyzes its operation, giving particular attention to the distribution of the benefits of integration and to the devices adopted to achieve an equitable distribution between the three-countries. Analyzes also, the 1967 Treaty for East African co-operation and discusses in detail the experience of its first seven years.